Healthcare Workers’ Knowledge and Resource Availability for Care of Sickle Cell Disease in Dar es Salaam, Tanzania - Jonathan, Agnes; Tutuba, Hilda; Lloyd, William; Ndunguru, Joyce; Makani, Julie; Ruggajo, Paschal; Minja, Irene K.; Balandya, Emmanuel (Frontiers in Genetics, 2022)
Background: Sickle cell disease (SCD) is a global public health priority due to its high morbidity and mortality. In Tanzania, SCD accounts for 7% of under-five mortality. Cost-effective interventions such as early diagnosis and linkage to care have been shown to prevent 70% of deaths but require knowledge among healthcare workers and availability of resources at health facilities. In Tanzania, data on these critical determinants is currently lacking. Objective: To assess healthcare workers’ knowledge and resource availability for care of SCD at health facilities in Dar es Salaam, Tanzania. Methodology: A facility-based cross-sectional study was conducted between December-2020 and February-2021 among 490 nurses and clinicians at Regional Referral Hospitals (Temeke, Amana, and Mwananyamala) and Muhimbili National Hospital in Dar es Salaam, Tanzania. Data was collected using pre-tested structured questionnaire consisting of 13 knowledge questions (scored good knowledge if correct response in >7) and an inventory check list to record available resources. Pearson’s Chi-square was used to determine association between level of knowledge and demographic factors. Multivariate logistic regression was used to ascertain the strength of associations. A two-tailed p-value < 0.05 was considered to be statistically significant. Results: Of the 490 participants (median age 28 years [IQR=26-35]), only 25.1% had good knowledge on SCD. The odds of good knowledge was 82% lower in nurses than clinicians (AOR= 0.177; 95% CI: 0.090, 0.349; p <0.001); 95% lower in Diploma than Masters degree holders (AOR = 0.049; 95% CI: 0.008, 0.300; p = 0.001) and 4.6 times higher in those with 5 – 9 years than ≥ 10 years of experience (AOR=4.564; 95%CI: 1.341, 15.525; p=0.015). The regional-level hospitals lacked diagnostic tests and Hydroxyurea therapy. Conclusion: There was general lack of knowledge on SCD among healthcare workers and limited availability of critical resources for the diagnosis and care of SCD, especially at regional-level hospitals. Efforts are needed for their improvement in order to enhance care to patients, thus reduce the morbidity and mortality due to SCD in Tanzania.